Pelatihan Budidaya Ikan Cupang (Betta sp.) di SMKN 1 Sebatik Barat Kalimantan Utara - Diana Purnama Sari; Rini Mastuti; Heppi Iromo; Aziz Aziz; Muhammad Amien; Ricky Febrinaldy Simanjuntak; Rukisah Saleh (Jurnal PKM Manajemen Bisnis, 2026)
Community Service was carried out at SMKN 1 Sebatik Barat on November 7, 2025, involving 30 students from the Aquaculture Agribusiness Program. The main objective of this activity was to develop students’ entrepreneurial character through betta fish (Betta splendens) farming activities. Betta fish farming was selected because it has promising business potential, requires relatively low capital investment, and can be easily implemented on a small scale. The program consisted of theoretical sessions covering good aquaculture practices, including broodstock selection, spawning techniques, fish rearing, basic business management, and marketing strategies for fishery products. Furthermore, students were directly involved in practical activities such as spawning and fry management. The results of the program indicated high participant enthusiasm and significant improvement in their understanding of aquaculture techniques and entrepreneurial concepts. The activity successfully fostered an entrepreneurial mindset, encouraged self-reliance, and provided practical skills that can be immediately applied to initiate small-scale fish farming businesses. This community service program is expected to serve as a sustainable first step in developing young entrepreneurs in the fisheries sector.